Characterizing the Gait of People With Different Types of Amputation and Prosthetic Components Through Multimodal Measurements: A Methodological Perspective - De Marchis, Cristiano; Ranaldi, Simone; Varrecchia, Tiwana; Serrao, Mariano; Castiglia, Stefano Filippo; Tatarelli, Antonella; Ranavolo, Alberto; Draicchio, Francesco; Lacquaniti, Francesco; Conforto, Silvia (Frontiers in Rehabilitation Sciences, 2022)
Prosthetic gait implies the use of compensatory motor strategies, including alterations in gait biomechanics and adaptations in the neural control mechanisms adopted by the central nervous system. Despite the constant technological advancements in prostheses design, that led to a reduction in compensatory movements and an increased acceptance by the users, a deep comprehension of the numerous factors that influence prosthetic gait is still needed. The quantitative prosthetic gait analysis is an essential step in the development of new and ergonomic devices, as well as to optimize the rehabilitation therapies. Nevertheless, the assessment of prosthetic gait is still carried out by a heterogeneous variety of methodologies, and this limits the comparison of results from different studies, complicating the definition of shared and well accepted guidelines among clinicians, therapists, physicians and engineers. This perspective article starts from the results of a project funded by the Italian Workers’ Compensation Authority (INAIL), that led to the generation of an extended dataset of measurements involving kinematic, kinetic, and electrophysiological recordings in subjects with different types of amputation and prosthetic components. By encompassing different studies published along the project activities, we discuss the specific information that can be extracted by different kinds of measurements, and we here provide a methodological perspective related to multi-modal prosthetic gait assessment, highlighting how, for designing improved prostheses and more effective therapies for patients, it is of critical importance to analyze movement neural control and its mechanical actuation as a whole, without limiting the focus to one specific aspect.